ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN PADA PERUSAHAAN J&T EXPRESS DI KOTA TIMIKA - Fitalis Tappi; Stepanus Sandy (ADISAM PUBLISHER, 2024)
This study aims to determine the effect of service quality on loyalty through customer satisfaction at the J&T Express company in Timika City. The research method used in this study is by using the associative method, and the data collection technique used is a questionnaire. The researcher used path analysis to analyze the effect of service quality on loyalty through customer satisfaction at the J&T Express company in Timika City. The results of the study showed that Tangibility, reliability, assurance had an effect on customer satisfaction. While Responsiveness and empathy did not affect customer satisfaction. Tangibility, reliability, assurance had an effect on customer loyalty. While Responsiveness and empathy had no effect on customer loyalty. There was no effect of customer satisfaction on loyalty. Tangibility, responsiveness, and empathy had no effect on loyalty through customer satisfaction. While Reliability and assurance had an effect on loyalty through customer satisfaction